The cogno-emotional learning in an elderly group - Corrales Camacho, Ismael (2018)
The course of Terapias de Aprendizaje en Grupo was taught during the year 2016 in the Programa de Atención Integral de la Persona Adulta Mayor (PAIPAM) of the Centro de Estudios Generales of the Universidad Nacional de Costa Rica. It was a participatory course aimed at the elderly adult population with interest in receiving cognitive and affective stimuli that would contribute even more to their healthy aging process. The course was approached from the disciplines of guidance and gerontology, with special emphasis on four types of therapies that were cognitive therapy, ludo therapy, laughter therapy and hug therapy. The focus of the work was on providing the adult and older adult a space for themselves where they could experience the social interaction of sharing joyful moments with others close to their age, while having fun streamlining their memory and generating a learning strategies against difficulties.